Unintended sunburn after sunscreen application: An exploratory study of sun protection. (4th November 2019) - O'Hara, Montana; Horsham, Caitlin; Koh, Uyen; Janda, Monika
Abstract: Issue addressed: This study explores the experiences of adults aged 18 years and older who received an unintended sunburn while wearing sunscreen and examines why the application of sunscreen as a sun protection measure did not work as intended. Methods: Qualitative content analysis was conducted on 11 interviews with people living in Australia who had received an unintended sunburn. Data were collected from July 2017 to January 2018. Twelve participants took part in individual semi‐structured interviews either face‐to‐face or over the telephone, and 11 participants met the eligibility criteria and were included for analysis. Results: The themes that emerged included experience of disbelief after sunburn; sunburn after water‐based activity; inaccurate sunscreen application; sunscreen acceptability and trust; discomfort in application, opportunistic sun exposure; aesthetically motivated behaviour; normative beliefs; and lack of awareness of recent sun safety campaigns. Conclusion: Participants perceived themselves as well protected from sun exposure and were surprised they received a sunburn. We found that participants did not reapply sunscreen often enough, especially before and during water activities and overestimated the amount of time they could be safely exposed to the sun. So what?: The findings of this study suggest a greater need for sun protection education on how to effectively use and apply sunscreen to avoid sunburn and skin cancer. Summary: This study explores the experiences of adults aged 18 years and older who received an unintended sunburn while wearing sunscreen and examines why the application of sunscreen as a sun protection measure did not work as intended. Qualitative content analysis was conducted on 11 interviews with people living in Australia who had received an unintended sunburn.